STUDENTS MISUNDERSTANDING OF THE NOTION OF LIMIT OF SEQUENCE - KLEPANCOVA, Michaela (Trends in education, 2015)
The concept of limit and especially its formal definition even in its simplest form - as a limit of a sequence - belongs in terms of learning process to difficult and problematic ones. Most students even after completion of course of Mathematical Analysis will not be able to completely understand the term of limit and their imagination of this concept does not correspond with the formal definition of limit. We can encounter various self-constructed definitions of students which may be caused due to an incomplete understanding or forgetting of learned definition of the limit of sequence, but in the end they does not meet the formal definition content. The contribution is focused on the identification of the most common formulations which students consider as correct. The contribution also points out the opportunity to prevent the students misconceptions in this term, alternatively to rectify them.
Keywords: notion of limit; formal definition of limit of sequence; calculus.